“MALIK” (APLIKASI MARKETPLACE BUSANA MUSLIM) - Hartono, Sugiarto; Hendrawan, Tommy; Pratama, Anang Ind (Infotech: Journal of Technology Information, 2023)
This study aims to carry out business planning and system design for the creation of a business startup marketplace based on a Muslim fashion mobile application with the name MALIK. The research method used is by using observation, questionnaires, interviews, and literature study. For system design, the approach method used is object-oriented analysis design. The results of this research will be a business plan in the form of business plan documentation complete with analysis using the business model canvas, industry analysis using Porter's Five Forces Model, and SWOT analysis. The next stage is to design a system in the form of a diagram with a unified modeling language notation, and a user interface. The results of the research that can be taken are that the target sample of customers is interested in Muslim clothing, buying Muslim clothing using the marketplace media with feature development carried out by MALIK in the form of online Muslim clothing tailoring, and virtual fitting rooms.